Factors Impacting the Use of Donation-Based Crowdfunding Platforms in Saudi Arabia: The Case of Ehsan Platform - Alshathry , Sahar; Albalawi II, Dr.Wafi (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2024)
This research investigates the factors influencing people's intentions to use donation-based crowdfunding platforms in Saudi Arabia, focusing on the Ehsan platform supervised by the Saudi Data and Artificial Intelligence Authority (SDAIA). Ehsan aims to ensure proper monetary distribution to genuinely needy individuals, thereby reducing financial fraud and corruption. For the platform's success, it is essential that citizens effectively utilize it. Employing the Unified Theory of Acceptance and Use of Technology, the study analyzes the determinants that influence intentions to use Ehsan and actual use behaviors. An empirical study was conducted with 224 Saudi citizens from various age groups, and the research model was validated using the Partial Least Squares (PLS) approach. Findings reveal that performance expectancy and facilitating conditions significantly impact intentions to use Ehsan, while effort expectancy and social influence do not. The results indicate a positive association between participants' intentions to use Ehsan and their actual usage. This study enhances the understanding of factors affecting donation-based crowdfunding platforms in Saudi Arabia and offers practical insights for platform developers and decision-makers to consider in their design and modifications.